2014
DOI: 10.6002/ect.2013.0300
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Objectives: To investigate the predictive value of urinary neutrophil gelatinase-associated lipocalin in the occurrence of delayed graft function after kidney transplant. Materials and Methods: In this prospective cohort study of 67 consecutive patients who received a living-related (40 patients [61%]) or deceased-donor kidney transplant (27 patients [39%]), urinary neutrophil gelatinase-associated lipocalin was determined in the first 100 mL perfusate of the donor kidney and in urine at 6 hours after transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
(22 reference statements)
1
4
0
Order By: Relevance
“…In line with previous studies, NGAL was a negative predictor for outcome after transplantation outcome [ 16 , 36 , 37 , 38 ]. Release of NGAL by distal tubular epithelial cells increases the severity of kidney injury such as IRI associated with transplantation.…”
Section: Discussionsupporting
confidence: 89%
“…In line with previous studies, NGAL was a negative predictor for outcome after transplantation outcome [ 16 , 36 , 37 , 38 ]. Release of NGAL by distal tubular epithelial cells increases the severity of kidney injury such as IRI associated with transplantation.…”
Section: Discussionsupporting
confidence: 89%
“…These findings let us speculate that NGAL is not only a marker of tubular damage but also a filtration marker, but this requires further investigation. NGAL was tracked in both serum and urine compared to several other studies describing only urinary NGAL expression [ 12 , 23 , 27 29 ]. In multivariate analyses we could show, that urinary NGAL as well as serum NGAL can significantly predict DGF on the second postoperative day but not creatinine.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that kidney epithelia express and excrete large quantities of NGAL into urine following acute injury, reaching up to 1000‐fold induction of NGAL mRNA and protein in the most severe cases 33. There is a large body of literature to indicate that uNGAL increases during the first posttransplant week in renal transplant recipients with DGF, especially in the very early urine samples collected within six h postsurgery 34, 35, 36. Thus, the main potential advantage arising from this finding is the possibility to identify and stratify patients according to their risk of dialysis need after transplant, prior to the diagnosis of DGF.…”
Section: Urinary Ngal and Dgfmentioning
confidence: 99%